The Living Fossil Psilotum nudum Has Cortical Fibers With Mannan-Based Cell Wall Matrix - Chernova, Tatyana; Ageeva, Marina; Mikshina, Polina; Trofimova, Oksana; Kozlova, Liudmila; Lev-Yadun, Simcha; Gorshkova, Tatyana (Frontiers in Plant Science, 2020)
Cell wall thickening and development of secondary cell walls was a major step in plant terrestrialization that provided the mechanical support, effective functioning of water-conducting elements and fortification of the surface tissues. Despite its importance, the diversity, emergence and evolution of secondary cell walls in early land plants have been characterized quite poorly. Secondary cell walls can be present in different cell types with fibers being among the major ones. The necessity for mechanical support upon increasing plant height is widely recognized; however, identification of fibers in land plants of early taxa is quite limited. In an effort to partially fill this gap, we studied the fibers and the composition of cell walls in stems of the sporophyte of the living fossil Psilotum nudum. Various types of light microscopy, combined with partial tissue maceration demonstrated that this perennial, rootless, fern-like vascular plant, has abundant fibers located in the middle cortex. Extensive immunodetection of cell wall polymers together with various staining and monosaccharide analysis of cell wall constituents revealed that in Psilotum, the secondary cell wall of its cortical fibers is distinct from that of its tracheids. Primary cell walls of all tissues in P. nudum shoots are based on mannan, which is also common in other extant early land plants. Besides, the primary cell wall contains epitope for LM15 specific for xyloglucan and JIM7 that binds methylesterified homogalacturonans, two polymers common in the primary cell walls of higher plants. Xylan and lignin were detected as the major polymers in the secondary cell walls of P. nudum tracheids. However, the secondary cell wall in its cortical fibers is quite similar to their primary cell walls, i.e., enriched in mannan. The innermost secondary cell wall layer of its fibers but not its tracheids has epitope to bind the LM15, LM6 and LM5 antibodies recognizing, respectively, xyloglucan, arabinan and galactan. Together, our data provide the first description of a mannan-based cell wall in sclerenchyma fibers, and demonstrate in detail that the composition and structure of secondary cell wall in early land plants are not uniform in different tissues.